Cytokinin deficiency confers enhanced tolerance to mild, but decreased tolerance to severe salinity stress in in vitro grown potato - Raspor, Martin; Mrvaljević, Miloš; Savić, Jelena; Ćosić, Tatjana; Kaleri, Abdul Rasheed; Pokimica, Nina; Cingel, Aleksandar; Ghalawnji, Nabil; Motyka, Václav; Ninković, Slavica (Frontiers in Plant Science, 2024)
Cytokinin (CK) is a plant hormone that plays crucial roles in regulating plant growth and development. CK-deficient plants are widely used as model systems for investigating the numerous physiological roles of CK. Since it was previously shown that transgenic or mutant CK-deficient Arabidopsis and Centaurium plants show superior tolerance to salinity, we examined the tolerance of three CK-deficient potato lines overexpressing the Arabidopsis thaliana CYTOKININ OXIDASE/DEHYDROGENASE2 (AtCKX2) gene to 50 mM, 100 mM, 150 mM, and 200 mM NaCl applied in vitro. Quantification of visible salinity injury, rooting and acclimatization efficiency, shoot growth, water saturation deficit, and chlorophyll content confirmed that the CK-deficient potato plants were more tolerant to low (50 mM) and moderate (100 mM) NaCl concentrations, but exhibited increased sensitivity to severe salinity stress (150 and 200 mM NaCl) compared to non-transformed control plants. These findings were corroborated by the data distribution patterns according to principal component analysis. Quantification of the activity of superoxide dismutases, peroxidases, and catalases revealed an impaired ability of AtCKX2-transgenic lines to upregulate the activity of antioxidant enzymes in response to salinity, which might contribute to the enhanced sensitivity of these potato lines to severe salt stress. Our results add complexity to the existing knowledge on the regulation of salinity tolerance by CK, as we show for the first time that CK-deficient plants can exhibit reduced rather than increased tolerance to severe salt stress.